Manajemen Risiko dalam Pendidikan: Tinjauan Literatur Sistematis Tentang Strategi, Praktik, dan Dampaknya Terhadap Ketahanan Organisasi - Dedi Kustiawan; Wieke Tsanya Fariati; Sri Nurhayati; Yani Nurani; Qubaila Fajrin Ega Soraya; Winda Sulastri; Rio Razab Isdendi (STIKes Ibnu Sina Ajibarang, 2025)
This systematic literature review explores the transformation of risk management practices in educational institutions, tracing the shift from fragmented, siloed approaches toward integrated Enterprise Risk Management (ERM) frameworks in response to globalization, technological disruption, and increasing regulatory demands. Using the PRISMA 2020 methodology, we reviewed and synthesized findings from 10 high-quality empirical studies published between 2020 and 2024, focusing on theoretical advancements, adaptive mechanisms in volatile educational contexts, and strategies for context-specific ERM implementation. The analysis indicates that the scope of risks in education has expanded significantly beyond traditional physical safety concerns to encompass reputational, operational, and psychosocial dimensions. These emerging risks are often driven by factors such as digital inequities, organizational complexities, and evolving policy landscapes. Three critical components are identified for effective ERM in educational settings: (1) risk integration that unifies financial, operational, and reputational considerations into a cohesive portfolio; (2) adaptive feedback loops that combine prospective scenario modeling, real-time AI-enabled monitoring, and retrospective learning from past crises; and (3) contextual customization, ensuring ERM frameworks are tailored to the unique characteristics, resources, and cultural dynamics of individual institutions. The study demonstrates that merging probabilistic risk theories with regulatory compliance standards, such as ISO 31000 and COSO, strengthens institutional resilience. Moreover, it highlights the importance of shifting from blame-oriented to learning-oriented post-crisis evaluations to foster a culture of continuous improvement. The proposed ERM framework bridges financial economics, institutional theory, and practice-based approaches, offering actionable strategies including real-time digital equity monitoring, stakeholder engagement protocols, and gamified disaster preparedness initiatives.By addressing gaps in the literature, this review makes both a theoretical and practical contribution to educational risk management. It provides a roadmap for mitigating contemporary challenges, such as resource allocation disparities, resistance to cross-institutional collaborations, and the protection of vulnerable school environments, ultimately supporting more resilient and adaptive educational systems.